Hysteresis Current Control of Single-Phase Single-Stage Grid-Connected Inverter with Buck-Boost Operation Capability - Komurcugil, Hasan; Güler, Naki; Bayhan, Sertac; Guzman, Ramon (IEEE Computer Society, 2023)
This paper presents a hysteresis current control for single-phase single-stage buck-boost grid-connected inverters. The inverter topology employs four switches that are operated with the grid frequency and two bidirectional switches that are operated with high switching frequency. Hence, unlike the existing single-stage inverter topologies, the switching losses are minimized. Moreover, this inverter configuration has the capability to operate both in buck and boost modes and utilizes only a single inductor. The proposed hysteresis current control eliminates the need for designing a dedicated modulation technique for this inverter topology. An active damping technique is utilized to cope with the resonance damping problem without employing additional sensor. The reference current needed in the hysteresis controller is produced using a proportional-resonant (PR) controller whose input is the grid current error. The use of PR controller guarantees zero steady-state error in the grid current. The validity and superiority of the proposed control method are confirmed by MATLAB/Simulink simulations under various operating conditions which include buck mode, boost mode, transition from boost mode to buck mode, reference current change and virtual resistor variation. The simulation results show that the proposed control method is able to transfer the desired current into grid successfully under all operating conditions. © 2023 IEEE.
49th Annual Conference of the IEEE Industrial Electronics Society, IECON 2023 -- 2023-10-16 through 2023-10-19 -- Singapore -- 194573
Keywords: buck-boost; grid-connected inverter; hysteresis current control; proportional-resonant control; Single-stage